Effects of levamisole, echinacea, and thyme oral administration on growth factors, blood parameters, and immunity in beluga, Huso huso. Issue 1 (2nd January 2019) - Eslami, Mahboubeh; Bahrekazemi, Masoumeh
ABSTRACT: A total of 180 fish (95.50 g) were fed with 0.1% levamisole, 0.5% thyme, and 0.5% echinacea crude extract for 60 days. The control group received no stimulant. The results of growth parameters indicated a significant positive effect of levamisole in comparison with the control group, though it was not significantly different from echinacea and thyme treatments (P > 0.05). No mortalities were observed in the treatments. Feed conversion ratio and protein efficiency ratio did not differ significantly between the treatments. The highest numbers of white and red blood cells and the greatest amounts of hemoglobin and hematocrit were detected in the levamisole treatment, showing significant differences with the other groups in the percentage of hemoglobin only (P < 0.05). The highest levels of MCH and MCHC were also measured in the levamisole treatment. Differential count of white blood cells revealed no significant differences in neutrophil and lymphocyte levels with the control. There was a significant increase in the percentage of eosinophil in the levamisole treatment alone. No significant differences were recorded in total protein, albumin, and aspartate aminotransferase and alanine aminotransferase enzymes. Levamisole treatment displayed the highest activities of glutathione peroxidase and lysozyme as well as the greatest amount of immunoglobulin. So 0.1 levamisole yielded better results in the growth, blood, and immunity parameters and can be used as a stimulant without injuring body organs.